2017
DOI: 10.1016/j.resp.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects on breathing of agonists to μ-opioid or GABA A receptors dialyzed into the ventral respiratory column of awake and sleeping goats

Abstract: Pulmonary ventilation (V̇I) in awake and sleeping goats does not change when antagonists to several excitatory G protein-coupled receptors are dialyzed unilaterally into the ventral respiratory column (VRC). Concomitant changes in excitatory neuromodulators in the effluent mock cerebral spinal fluid (mCSF) suggest neuromodulatory compensation. Herein, we studied neuromodulatory compensation during dialysis of agonists to inhibitory G protein-coupled or ionotropic receptors into the VRC. Microtubules were impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Doi and Ramirez tested the concept of neuromodulator interdependence where changes in one or more neuromodulators are compensated for by changes in other modulators to maintain stability in the respiratory control network (7,8). Subsequent studies support this concept as compensatory neuromodulation was elicited by dialysis of agonists/antagonists in the respiratory rhythm/pattern-generating VRC of awake and sleeping goats (20,21,(32)(33)(34)(35). The objective herein was to study this concept as it applies to the motor neuron-rich HMN, focusing on effects of activating -opioid receptors (DAMGO) or inhibiting musca- rinic (atropine), neurokinin-1 (spantide) and select serotonergic receptors (5-HT 2A ; MDL 11,939).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Doi and Ramirez tested the concept of neuromodulator interdependence where changes in one or more neuromodulators are compensated for by changes in other modulators to maintain stability in the respiratory control network (7,8). Subsequent studies support this concept as compensatory neuromodulation was elicited by dialysis of agonists/antagonists in the respiratory rhythm/pattern-generating VRC of awake and sleeping goats (20,21,(32)(33)(34)(35). The objective herein was to study this concept as it applies to the motor neuron-rich HMN, focusing on effects of activating -opioid receptors (DAMGO) or inhibiting musca- rinic (atropine), neurokinin-1 (spantide) and select serotonergic receptors (5-HT 2A ; MDL 11,939).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, conformational changes in opioid receptors cause coupling to inhibitory G proteins when exposed to high opioid concentration, whereas the same receptor subtype might switch to a stimulatory G protein during exposure to low opioid concentrations (11,49). Opioids modulate neural activity throughout the central nervous system, including the preBötC and HMN (10,18,20,48). The effects of opioid administration in the preBötC, critical for the generation of respiratory rhythm and pattern (18,21), have been equivocal, where some studies found breathing increases (20,36), breathing decreases (28,29), or no effect (18,20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations